It takes a village - asthma networks utilized by parents when managing childhood asthma medications. (3rd March 2020) - Srour-Alphonse, Pamela; Cvetkovski, Biljana; Rand, Cynthia S.; Azzi, Elizabeth; Tan, Rachel; Kritikos, Vicky; Cheong, Lynn H. M.; Bosnic-Anticevich, Sinthia
Abstract: Objective: We are yet to understand how widely parents seek asthma medication management information for their children, how they are used for health information, how parents engage with them and their influence on parent's decision-making. This study aimed to gauge the current level of asthma knowledge and skills of parents of children with asthma and gain insight into who and what influences their child's asthma medication management decisions. Method: Social network theory was used to map parents' asthma networks and identify the level of influence of each individual/resource nominated. Parents of children with asthma (aged 4–18 years) were interviewed, completed an asthma network map, questionnaires and an inhaler technique assessment. Results: Twenty-six parents participated and had significant gaps in asthma knowledge and inhaler technique skills. The asthma networks of participants ranged from two to ten individuals/resources, with an average number of five. The most commonly nominated individual/resource was general practitioners followed by family members and the internet. Professional connections represented 44% of individuals/resources in networks, personal connections 42% and impersonal connections 14%. When parents were asked about how influential individuals/resources were, professional connections represented 53% of parents influences, personal connections 36% and impersonal connections 11%. Conclusion: This study highlights the priority and co-influence of non-medical sources of information/support on parent's behaviors and decision-making with regards to their child's asthma medicine taking. In further understanding the complexities surrounding these connections and relationships, HCPs are better positioned to assist parents in addressing their needs and better supporting them in the management of their child's asthma.